NORM BOUNDS FOR CONTRACTIVE NORMALOID OPERATORS - Okelo, N. B. (Journal of Global Research in Mathematical Archives(JGRMA), 2017)
In this paper we establish the upper and lower norm estimates of contractive normaloid operators using inner product, Schwarz inequality for non-negative real numbers and some operator inequalities. Â Keywords: Normaloid operators, Contractive operators, inner product, Schwarz inequality and numerical radius. Â